2019
DOI: 10.31219/osf.io/qfj5y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of religious beliefs and collective narcissism in interreligious contact on university students

Abstract: The rise of exclusive puritanism movements challenges several communities to live in peaceful coexistence. This research aimed to observe the level of interreligious contact on university students. This was a threefold study. The first part was an initial inquiry to construct an interreligious contact scale. The second sought to see the inferential association between interreligious contact, belief in religious teachings (i.e. fundamental religious belief, kindly religious belief, and meta-religion endorsement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…People who believed strongly in the truth inscribed in their religious scriptures were likely to exhibit lower tolerance towards atheists. A number of other studies have also reported similar findings: the more literally people interpret their religious teachings, the higher their prejudice against outgroups and the lower their tendency to engage with other religions ( Ardi and Budiarti, 2020 ; Hunsberger and Jackson, 2005 ; Küpper and Zick, 2011 ; Wrench et al., 2006 ). Ardi and Budiarti's (2020) study demonstrated a negative association between religious fundamentalism and contact with outgroups.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…People who believed strongly in the truth inscribed in their religious scriptures were likely to exhibit lower tolerance towards atheists. A number of other studies have also reported similar findings: the more literally people interpret their religious teachings, the higher their prejudice against outgroups and the lower their tendency to engage with other religions ( Ardi and Budiarti, 2020 ; Hunsberger and Jackson, 2005 ; Küpper and Zick, 2011 ; Wrench et al., 2006 ). Ardi and Budiarti's (2020) study demonstrated a negative association between religious fundamentalism and contact with outgroups.…”
Section: Discussionmentioning
confidence: 56%
“…A number of other studies have also reported similar findings: the more literally people interpret their religious teachings, the higher their prejudice against outgroups and the lower their tendency to engage with other religions ( Ardi and Budiarti, 2020 ; Hunsberger and Jackson, 2005 ; Küpper and Zick, 2011 ; Wrench et al., 2006 ). Ardi and Budiarti's (2020) study demonstrated a negative association between religious fundamentalism and contact with outgroups. Religious scriptures offer a frame of reference through which believers can interpret reality so that they can establish goals and build relationships with other groups ( Hunsberger and Jackson, 2005 ).…”
Section: Discussionmentioning
confidence: 56%
“…We indicate the estimations for the dependent variables of the models used in the empirical study and complementary information using Regression Analysis as Ardi and Budiarti (2020) in their study about the role of religious beliefs and collective narcissism in interreligious contact on university students.…”
Section: Methodsmentioning
confidence: 99%